ETHICAL INTEGRATION OF AI IN ANIMATION STUDIES: FOSTERING LIFELONG LEARNING, RESPONSIBLE DECISION-MAKING, AND HUMAN CREATIVITY - Muhammad Cahya Mulya Daulay; Mega Iranti Kusumawardhani (Institut Seni Budaya Indonesia Bandung, 2024)
This paper explores the ethical integration of artificial intelligence (AI) in animation studies, focusing on empowering undergraduate students as lifelong learners. The research aims to provide practical guidance for undergraduate animation students to ethically integrate AI technologies into their learning and creative processes while fostering responsible decision-making and promoting the preservation of human creativity. The study employs a desk research methodology, gathering and analyzing relevant literature and scholarly sources in AI ethics and animation studies. The main findings of the research highlight the importance of critical thinking and responsible decision-making when incorporating AI tools into the creative process. It emphasizes addressing ethical challenges such as authorship, bias, transparency, and appropriation in utilizing AI technologies. The research also delves into the ethical implications of generative AI, including considerations of originality and the balance between human creativity and AI capabilities. The implications of the research findings underscore the significance of lifelong learning and adaptability for undergraduate students to keep pace with AI advancements and ensure ongoing ethical development as creators and innovators in animation. By promoting the ethical integration of AI technologies, students can navigate the challenges of AI utilization while preserving the integrity of their creative expression. The research contributes to understanding ethical considerations in integrating AI in animation studies. It provides practical insights for students and educators in fostering responsible and innovative use of AI technologies.